Numerical Study of Savonius Wind Turbine Performance at Tidar University under Wind Speed and Direction Angle Using the CFD Method - Ahmad Izzudin Robani; Nurmala Dyah Fajarningrum; Raka Mahendra Sulistiyo; Fuad Hilmy; Andriyatna Agung Kurniawan (Mechanical Engineering Department - Semarang State Polytechnic, 2026)
The savonius wind turbine is a type of vertical axis wind turbine (VAWT) that operates based on the drag force principle. Its simple design, featuring S-shaped blades arranged around a vertical shaft, enables the turbine to capture wind from any direction and operate effectively at low wind speeds, making it suitable for residential areas. This study investigates the performance of a three-bladed helical Savonius turbine with a 180° twist angle under variations in wind speed and wind direction. Numerical simulations were conducted using Computational Fluid Dynamics (CFD). Wind speed data were obtained from rooftop measurements at the Faculty of Economics, Tidar University, recorded at 08:00, 10:00, 12:00, 14:00, and 16:00, with average values of 1.9 m/s, 2.0 m/s, 2.2 m/s, 2.2 m/s, and 2.0 m/s, respectively. The analyzed wind direction angles were 15 , 25 , and 35 . Results show that a 15 wind direction produced the most stable and optimal performance, achieving a turbine power ( ) of 0.0356 W, a power coefficient (Cp) of 0.0931, and a TSR of 0.525. This occurred because the airflow aligned more effectively with the rotor, improving kinetic energy capture, reducing drag flow on the convex returning blade, and minimizing vortex formation and negative torque. Peak performance occurred at 12:00 and 14:00 when wind speeds exceeded 2.0 m/s. However, the power coefficient showed a decreasing trend due to the presence of adverse flow phenomena that reduce the amount of wind energy converted by the turbine.